2019
DOI: 10.1111/ajr.12519
|View full text |Cite
|
Sign up to set email alerts
|

Client, provider and community referrer perceptions of telehealth for the delivery of rural paediatric allied health services

Abstract: Objective: To examine allied health client, provider and community referrer perceptions of telehealth for the delivery of rural paediatric allied health services to facilitate adoption. Design: A qualitative design employed semistructured interviews with the three key stakeholder groups. Setting: Stakeholders were associated with BUSHkids (The Royal Queensland Bush Children's Health Scheme), a not-for-profit organisation serving children and families in Queensland, Australia. Participants: Thirty-nine stakehol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
72
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(74 citation statements)
references
References 18 publications
1
72
0
1
Order By: Relevance
“…This strategy to involve family members who are the main daily caregivers to the hypertensive patients and equip them with better patient‐family partnership in hypertension care, can be applied to rural context generally and in developed countries, such as Australia. To provide efficient and ongoing daily care of people with chronic illnesses such as hypertension and to address the peculiar and specific behavioural norms of rural culture, a therapeutic and supportive family context and partnership can be crucial and important, 35 despite the fact that telehealth can benefit to patients and families in some rural areas where internet or teleconferencing connection and communication can be available and affordable 36 . This family‐oriented model of hypertension management applied to rural areas can bring better physical and psychological outcomes for both patients and their family caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…This strategy to involve family members who are the main daily caregivers to the hypertensive patients and equip them with better patient‐family partnership in hypertension care, can be applied to rural context generally and in developed countries, such as Australia. To provide efficient and ongoing daily care of people with chronic illnesses such as hypertension and to address the peculiar and specific behavioural norms of rural culture, a therapeutic and supportive family context and partnership can be crucial and important, 35 despite the fact that telehealth can benefit to patients and families in some rural areas where internet or teleconferencing connection and communication can be available and affordable 36 . This family‐oriented model of hypertension management applied to rural areas can bring better physical and psychological outcomes for both patients and their family caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…Participants in the study also reported a lack of physical touch and a reduction in the personal rapport that is built when there is face‐to‐face contact as barriers to accepting eHealth allied health services 33 . Interestingly, no participants identified technology difficulties as a barrier to accessing eHealth services 33 . While the current study did not explore the reasons for only accessing face‐to‐face services, it would seem logical that technological access was not the primary barrier to accessing non‐traditional (ie telehealth) therapy services given the mode of survey delivery.…”
Section: Discussionmentioning
confidence: 99%
“…In rural and remote settings, optimal access might include shifting from the traditional method of allied health service delivery that relies on either therapists or recipients travelling distances to provide and access services to telehealth delivery of services 33 . Embracing alternative methods such as telehealth services was not an option to improve service delivery to regional, rural and remote in earlier studies, 7,8,10 but it is an avenue that certainly requires continued expansion given the impact of COVID‐19 on access to allied health services.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations